Performance, ingestive behavior and carcass traits of lambs fed rations containing soybean cake - Adílson Sponchiado (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to evaluate the performance, ingestive behavior and carcass traits of crossbred Dorper x Santa Inês lambs fed rations containing soybean cake. Twenty-four lambs (4 months of age and 24.3 ± 3.1 kg BW) were used in a completely randomized design with four treatments and six replicates. Treatments were the inclusion of 50, 100 or 150 g kg-1 of soybean cake in the ration, on a DM basis, and a control diet without this ingredient. Rations were offered ad libitum for 75 days and the lambs were slaughtered at 35 to 40 kg BW. Dry matter intake reduced linearly and the average daily gain had a quadratic response to the soybean cake levels, also decreasing with the addition of this ingredient. The time spent feeding increased and the idle time decreased linearly with the soybean cake levels, whereas the time spent in rumination was not affected. Hot and cold carcass weights decreased linearly with the addition of this ingredient. The addition of 50 to 150 g kg DM-1 of soybean cake to the ration for lambs is not recommended due to reduced animal performance, which may compromise the profitability of sheep farmers.